2019
DOI: 10.1002/chem.201903952
|View full text |Cite
|
Sign up to set email alerts
|

Adsorptive Separation of Acetylene from Ethylene in Isostructural Gallate‐Based Metal–Organic Frameworks

Abstract: The separation of acetylene from ethylene is of paramount importancei nt he purification of chemicalf eedstocks fori ndustrial manufacturing. Herein, an isostructural series of gallate-based metal-organic frameworks (MOFs), Mgallate (M = Ni, Mg, Co), featuring three-dimensionallyi nterconnected zigzag channels, the aperture size of which can be finely tunedw ithin 0.3 by metalr eplacement. Controlling the apertures ize of M-gallate materials slightly from 3.69 down to 3.47 could result in ad ramatic enhancemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 76 publications
5
17
0
Order By: Relevance
“…23 Notably, Mgallate were also found to display excellent performance in the adsorption separation of C 2 H 2 from C 2 H 4 as a result of supramolecular interactions and steric effect. 24 On the whole, these results indicate the potential of this series of gallate-based MOFs to affect the separation mixtures of hydrocarbons with comparable sizes through shape-selective separation, which generally depends on the subtle matching of the shape and size of the adsorbates with the micropores of adsorbent. Herein, we explore the ability of M-gallate (M = Ni, Mg, Co) to separate C 4 mixtures and find that they display excellent performance for the adsorption separation of trans/cis-2-butene and 1,3butadiene, 1-butene, and iso-butene with record-high selectivity.…”
Section: ■ Introductionmentioning
confidence: 79%
“…23 Notably, Mgallate were also found to display excellent performance in the adsorption separation of C 2 H 2 from C 2 H 4 as a result of supramolecular interactions and steric effect. 24 On the whole, these results indicate the potential of this series of gallate-based MOFs to affect the separation mixtures of hydrocarbons with comparable sizes through shape-selective separation, which generally depends on the subtle matching of the shape and size of the adsorbates with the micropores of adsorbent. Herein, we explore the ability of M-gallate (M = Ni, Mg, Co) to separate C 4 mixtures and find that they display excellent performance for the adsorption separation of trans/cis-2-butene and 1,3butadiene, 1-butene, and iso-butene with record-high selectivity.…”
Section: ■ Introductionmentioning
confidence: 79%
“…Accordingly, the single-component adsorption-desorption isotherms for C 2 H 2 , CO 2 , and CH 4 were collected at three different temperatures of 278 K, 288 K, and 298 K and pressures up to 1 atm (Figure 3). The adsorption branches were overlapped with the desorption ones for all isotherms, indicating the ad- , [12] MOF-5 (26 cm 3 (STP) g -1 ), [12] BSF-1 (52.6 cm 3 (STP) g -1 ), [13] [Zn 12 (tdc) 6 (glycerol) 6 (dabco) 3 ] (55.1 cm 3 (STP) g -1 ), [14] UTSA-36 (56.8 cm 3 (STP) g -1 ), [15] Cu 2 (bdc) 2 (dabco) (60 cm 3 (STP) g -1 ), [16] Mg(HCOO) 2 (66 cm 3 (STP) g -1 ), [17] (Me 2 NH 2 ) 2 [Zn 6 (TBAPy) 2 (Ade-NH 2 ) 4 (μ 4 -O)] (69.4 cm 3 (STP) g -1 ), [18] CPL-2 (70 cm 3 (STP) g -1 ), [19] SIFSIX-3-Ni (74 cm 3 (STP) g -1 ), [6] UTSA-220 (76 cm 3 (STP) g -1 ), [20] Ni-gallate (80.4 cm 3 (STP) g -1 ), [21] and TIFSIX-2-Cu-i (91.8 cm 3 (STP g -1 ). [6] To our delight, ZJNU-8 adsorbed much more amount of C 2 H 2 than CO 2 and CH 4 especially at the low pressure.…”
Section: Resultsmentioning
confidence: 99%
“…A study by Rahim et al (2020) reported the preparation of an adsorbent from the combination of TA/Zn(IV) MPN for capturing heavy metal contaminants in wastewater 14 . Wang et al (2019) assembled Ni-, Mg-, and Co-gallate with a tunable aperture for the adsorption and separation of acetylene from ethylene 15 . Within the range of available phenolic linkers, TA, gallic acid (GA), and polydopamine (PDA) are the widely used linker for MPN synthesis 16 19 .…”
Section: Introductionmentioning
confidence: 99%